The Impact of Hate Speech Regulations on Freedom of Expression an Indonesian Legal Perspective - Muslim, Shohib; Solapari, Nuryati (The Easta Journal Law and Human Rights, 2024)
This paper explores the impact of hate speech regulation on freedom of expression in Indonesia from a juridical perspective. The study focuses on the legal framework, including the Electronic Information and Transactions Law (UU ITE) and the Indonesian Penal Code (KUHP), both of which are central to the regulation of hate speech. Through an analysis of key statutes, court rulings, and case studies, this paper highlights the tension between protecting public order and safeguarding free speech. The findings reveal that vague legal definitions and broad enforcement of hate speech laws have led to selective prosecution, often targeting political dissent and criticism. These issues raise concerns about the erosion of democratic rights and the potential misuse of hate speech laws for political purposes. Recommendations are provided to clarify legal definitions, ensure proportionality in enforcement, and prevent the misuse of these laws in a manner that balances the protection of social harmony with the preservation of freedom of expression.